2008
DOI: 10.1177/1468798408096479
|View full text |Cite
|
Sign up to set email alerts
|

Teacher flexibility and judgment: A multidynamic literacy theory

Abstract: In an age of restrictive standards and accountability measures, teachers often find themselves in a position where they have to struggle to keep play with language and literature as a focus of their early literacy instruction, as 'scientifically based' reading programs, phonics, or scripted instruction take center stage. In order to counter this trend, this article offers a 'multidynamic' theory for early literacy instruction that combines researched foundations of early reading success with sociocultural theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
13
0
3
Order By: Relevance
“…For instance, scripted content delivery may result in "thoughtless" instruction in which teachers do not reflect on, critique, or sufficiently modulate instruction to meet the situational needs of students (Allington, 2002;Hassett, 2008) resulting in less student reading growth.…”
Section: The Importance Of Content-delivery Structure Especially In mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, scripted content delivery may result in "thoughtless" instruction in which teachers do not reflect on, critique, or sufficiently modulate instruction to meet the situational needs of students (Allington, 2002;Hassett, 2008) resulting in less student reading growth.…”
Section: The Importance Of Content-delivery Structure Especially In mentioning
confidence: 99%
“…instruction to meet the situational needs of students (Allington, 2002;Hassett, 2008) resulting in less student reading growth.…”
mentioning
confidence: 99%
“…The top-down initiatives often did not take into account individual students' needs or teachers' pedagogical preferences (Harper et al 2008;Hassett 2008), a phenomenon that has been reported on in other countries (e.g., Bloch et al 2010;Hélot and Young 2006;Valdivieso 2010). For example, in a recently-published volume, several researchers in different countries describe how teachers were expected, to varying degrees, to surrender their professional agency to individuals and institutions that oversaw their work (Menken and García 2010b).…”
mentioning
confidence: 99%
“…Also, school-wide efforts to enforce such programs have been shown to result in pedagogical environments that jeopardize the literacy learning opportunities available to students, including those serving ELs in high poverty schools (GerstlPepin and Woodside-Jiron 2005;Hassett 2008;Sunderman et al 2005). Now that NCLB is up for reauthorization by the U.S. Congress and Reading First funding has come to an end, there is speculation about policies that the federal government will develop to improve the literacy education of low-income students and ELs.…”
mentioning
confidence: 99%
“…Além disso, quando os professores iniciam atividades abertas em relação aos textos multimodais, eles criam um espaço para valorizar as diferenças linguísticas e culturais entre os alunos em sala de aula (HASSETT, 2008 Novas habilidades para ler, buscar informação, autenticar e manipular informação, vincular e recontextualizar informação são exigidas neste ambiente multimodal (BEAVIS, 2006;KRESS, 2003;LUKE, 1996). Junto com a escolha de qual modo utilizar na leitura, a estrutura de muitos textos digitais abre opções sobre onde começar a ler, e qual caminho tomar para a leitura de um texto.…”
Section: Multimodalidade No Ensinounclassified